Posted by **ROCKY** on Thursday, July 28, 2011 at 12:07pm.

In solving the equation (x-1)(x+2)=30. Eric stated that the solution would be

x-1=30¨T¡úx=31 or(x-2)¨T30¨T¡úx=32 However, at least on of these solutions fails to work when subsitituted back into the orignal equation. Why is that? Please help Eric to understand better, solve the problem yourself, and explain your reasoning.

## Answer This Question

## Related Questions

- Algebra - In solving the equation (x + 3)(x + 1) = 48, Eric stated that the ...
- algebra - 1. In solving the equation (x + 3)(x + 1) = 48, Eric stated that the ...
- math - In solving the equation (x + 4)(x – 7) = -18, Eric stated that the ...
- algbera - In solving the equation (x + 3)(x + 1) = 48, Eric stated that the ...
- intermediate algebra - in solving the equation (x+4)(x-4)=9 eric stated the ...
- algebra - in solving the equation (x +2)(x - 2) = 32 eric stated the solution to...
- Intermediate Algebra - solve equation (x+1)(x-2)=54 Eric stated that the ...
- Math - I don't understand how to solve this problem: In solving the equation (x...
- Math - In solving the eqaution(x+4)(x-4),Eric stated thatthe solution would be x...
- algebra - solving the equation (x+4)(x-4)=9 Eric stated that the solution would ...

More Related Questions